Studi Penggunaan Albumin pada Pasien Gagal Ginjal Kronik (GGK) di RSUD Sidoarjo: Drug Utilization Study of Albumin Use in Patients with Chronic Kidney Disease (CKD) at Sidoarjo Regional Hospital - Bastari, Nadya Kirana Savira; Mukti, Asri Wido; Purbosari, Ira (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2024)
In patients with Chronic Renal Failure (CKD), protein loss in urine results in albumin levels <2.5 g/dL, requiring albumin therapy. The purpose of this study was to assess the accuracy of albumin therapy in patients with CKD, including: albumin concentration, albumin dose, duration of administration, therapy outcome, and to determine the presence or absence of Drug Related Problems (DRPs). The research conducted refers to the time limited sampling method, descriptive analysis, using non-experimental observation, and relevant data collected through retrospective methods for the period 01 October-31 December 2022 at Sidoarjo Regional Hospital. In this study, there were 23 patients who met the inclusion criteria. Albumin used two types of concentrations, 20% and 25% (100 ml preparation) with a dose of 1×1 intravenous route (IV) drip and duration of administration <4 hours. Therapeutic outcomes that reached the target were 48% and did not reach the target 52%. The 4 DRPs analysed included: drug interaction, drug indication, dose appropriateness, and untreated indication. Of the 4 DRPs, 3 DRPs including: drug interactions, drug indications, and dose conformity were declared no DRPs and 1 DRPs in the category of untreated indications had DRPs. The results of the study showed that the use of 20% and 25% albumin in hypoalbuminemia CKD patients at Sidoarjo Regional Hospital was appropriate and could increase albumin levels in CKD patients. Keywords: Albumin, Chronic Kidney Disease (CKD), Drug Utilization Study (DUS) Abstrak Pada pasien Gagal Ginjal Kronik (GGK) kehilangan protein dalam urine mengakibatkan kadar albumin <2,5 g/dL, sehingga memerlukan terapi albumin. Tujuan penelitian ini menilai ketepatan terapi albumin pada pasien GGK, mencakup : konsentrasi albumin, dosis albumin, durasi pemberian, outcome terapi, dan untuk mengetahui ada atau tidaknya Drug Related Problems (DRPs). Penelitian yang dilakukan mengacu metode time limited sampling, dianalisis deskriptif, menggunakan observasi non-eksperimental, dan data 23 pasien yang memenuhi kriteria inklusidikumpulkan melalui metode retrospektif periode 01 Oktober-31 Desember 2022 di RSUD Sidoarjo. Albumin yang digunakan dua jenis konsentrasi, 20% dan 25% (sediaan 100 ml) dengan dosis 1x1 rute intravena (IV) drip dan durasi pemberian <4 jam. Outcome terapi yang mencapai target sebesar 48% dan tidak mencapai target 52%. Untuk 4 DRPs yang dianalisis, meliputi: interaksi obat, indikasi obat, kesesuaian dosis, dan indikasi yang tidak diobati. Dari keempat DRPs tersebut, terdapat 1 DRPs yang teridentifikasi yaitu tidak diobati. Hasil dari penelitian menunjukkan penggunaan albumin 20% dan 25% pada pasien GGK hipoalbuminemia di RSUD Sidoarjo sudah sesuai dan dapat meningkatkan kadar albumin pada pasien GGK. Kata Kunci: Albumin, Gagal Ginjal Kronik (GGK), Studi Penggunaan Obat